2016
DOI: 10.1139/cjpp-2015-0394
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor enhances the CRE-dependent transcriptional activity activated by nobiletin in PC12 cells

Abstract: Keyword:alzheimer disease, CRE-dependent transcription, nerve growth factor, nobiletin, PC12 cells https://mc06.manuscriptcentral.com/cjpp-pubs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Nagase et al previously reported that nobiletin inhibits the phosphodiesterase (PDE) activity catalyzing the hydrolysis of cAMP, thereby increasing the intracellular cAMP concentration to activate PKA in PC12D cells [69]. Moreover, nobiletin induced CREB phosphorylation in an ERK kinase (MEK)/ERK-dependent manner [19,70,71]. Of note, it also reversed the sublethal Aβ-induced decrease in CREB phosphorylation in cultured hippocampal neurons [23].…”
Section: Effects Of Nobiletin In Cultured Cells and Slicesmentioning
confidence: 99%
“…Nagase et al previously reported that nobiletin inhibits the phosphodiesterase (PDE) activity catalyzing the hydrolysis of cAMP, thereby increasing the intracellular cAMP concentration to activate PKA in PC12D cells [69]. Moreover, nobiletin induced CREB phosphorylation in an ERK kinase (MEK)/ERK-dependent manner [19,70,71]. Of note, it also reversed the sublethal Aβ-induced decrease in CREB phosphorylation in cultured hippocampal neurons [23].…”
Section: Effects Of Nobiletin In Cultured Cells and Slicesmentioning
confidence: 99%
“…Nobiletin is a PMF mainly found in the peel of citrus fruit [ 18 ] and in fruit pulp. It has been reported to improve various disorders such as Alzheimer’s disease [ 19 , 20 ], inflammation, and metabolic syndrome [ 21 24 ] in animals. Recently, a relationship between nobiletin, obesity, and circadian rhythm in mice has been reported [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pathways related to nobiletin in cognitive dysfunction. Nobiletin protects hippocampal neurons through the cAMP/PKA/ERK/CREB signalling pathways and improves learning and memory ability [ 11 , 24 , 38 , 39 , 58 ]. Nobiletin and nerve growth factor act together to increase the phosphorylation level of ERK and activate CRE-dependent transcription [ 58 ].…”
Section: Effect and Mechanisms Of Nobiletin In The Cnsmentioning
confidence: 99%
“…Nobiletin protects hippocampal neurons through the cAMP/PKA/ERK/CREB signalling pathways and improves learning and memory ability [ 11 , 24 , 38 , 39 , 58 ]. Nobiletin and nerve growth factor act together to increase the phosphorylation level of ERK and activate CRE-dependent transcription [ 58 ]. Intraperitoneal injection of 10 or 50 mg/kg 4-demethylnobiletin can improve NMDA receptor dysfunction-induced cognitive dysfunction via the PKA/ERK/CREB pathway [ 2 ].…”
Section: Effect and Mechanisms Of Nobiletin In The Cnsmentioning
confidence: 99%